IMPLIKASI TEORI BUNGA TERHADAP MANAJEMEN KEUANGAN DALAM PERSPEKTIF EKONOMI ISLAM - M. Nuruddin Umar; Mohammad Naim Musafik; Arisyahidin Arisyahidin (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This study aimed to describe the implications of the theory of interest to financial management. Results of the description viewed from the standpoint of Islamic economics. The implication variable that really stood out are theory of interest; interest philosophy, the concept of interest and usury, the concept of money, the concept of time value of money and the economic value of time, the concept of cost of capital, and interest as a revenue. The variables in financial management implicated by of the theory interest are the general economic, investment, pricing, inflation and money supply, economic growth, unemployment, social welfare and exchange rate. This study is a literature research (library research), which is using books as a source of data to explain the issues studied. The character of this study is descriptive qualitative research that describe and analyze the data clearly on the theories of interest and their implications to financial management on the Islamic economics perspective. Source of data used in this research is secondary data, ie data obtained from the study of literature in the form of analysis of books, papers and websites. According to the type of data that is required of the study, the data analysis technique used is the technique of "content analysis" which is a method of data analysis that focuses on the content of an object of study. In addition to using content analysis method, the author also uses several methods of approach, namely: Deduction Approach, Induction Approach and Comparison. From the discussion, this study found strong implications of the theory of interest to financial management, and after review of the economic point of view Islam concluded there is a negative impact on the economic system of conventional, for example, that in fact the theory of interest is the intervention of theoretical biology, so it is considered living creature that is about living cells, the concept of money, it is not clear status; instrument or commodity?, The interest is riba, time value of money is not rational, the right is economic value of time, including capital costs and the interest is considered as an income. The findings impact to the financial management so that the economic system is not clear (absurd).